Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1111/j.1528-1157.1998.tb01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Nonconvulsive Status Epilepticus After the Control of Convulsive Status Epilepticus

Abstract: Summary:Purpose: Convulsive status epilepticus (CSE) is a major medical and neurological emergency that is associated with significant morbidity and mortality. Despite this high morbidity and mortality, most acute care facilities in the United States cannot evaluate patients with EEG monitoring during or immediately after SE. The present study was initiated to determine whether control of CSE by standard treatment protocols was sufficient to terminate electrographic seizures.Methods: One hundred sixty-four pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
306
0
15

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(340 citation statements)
references
References 28 publications
(23 reference statements)
16
306
0
15
Order By: Relevance
“…Multivariate regression revealed a doubling in the odds of mortality among these patients who transitioned to nonconvulsive status epilepticus and an independent doubling in the odds of mortality among patients >60 years of age [63].…”
Section: Status Epilepticusmentioning
confidence: 91%
See 2 more Smart Citations
“…Multivariate regression revealed a doubling in the odds of mortality among these patients who transitioned to nonconvulsive status epilepticus and an independent doubling in the odds of mortality among patients >60 years of age [63].…”
Section: Status Epilepticusmentioning
confidence: 91%
“…After the convulsive status subsides, 30% of those patients with subtle or nonconvulsive seizures develop nonconvulsive status epilepticus [63]. Status epilepticus itself results in 21% mortality, with age (odds ratio [OR], 1.1) and acute symptomatic cause for the seizure activity (OR, 6.0) found to be multivariate predictors of mortality.…”
Section: Status Epilepticusmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of patients appropriately treated for convulsive SE found that 48% went on to have continued nonconvulsive seizures and 15% were diagnosed with NCSE, underscoring the importance of continuous EEG to identify RSE and guide its treatment. 42 Although data are limited, more recent studies estimate that 23 to 43% of patients in SE will progress to RSE, and the mortality of RSE ranges from 17 to 39%. 22,[43][44][45][46] Similar to nonrefractory SE, mortality is largely dependent on the underlying etiology for RSE and the patient's age.…”
Section: Refractory Status Epilepticus and Superrefractory Status Epimentioning
confidence: 99%
“…The incidence of NCS and NCSE ranges between 8 and 48% depending on the patient population studied [1][2][3][4][5][6][7][8]. The mortality rate of neurologically critically ill patients afflicted with NCSE is 18-57% [9,10] while the presence of NCS is associated with a mortality rate of 33% [10].…”
Section: Introductionmentioning
confidence: 99%